Impact of Ambient Temperature, Passenger Load, and Delay on the Consumption of Battery Electric Buses - Szilassy, Péter Ákos; Földes, Dávid (Periodica Polytechnica Transportation Engineering, 2024)
The operation of state-of-the-art battery electric buses (BEBs) has started recently, and their consumption model is unknown. Therefore, the service providers are lenient regarding the energy used. Our aim was to reveal the effects of ambient temperature and bus service characteristics, such as passenger load and delay, on the energy consumption. Real-time consumption data of BEBs were analyzed in Nyíregyháza, Hungary, and the functional relationships among the aforementioned variables were revealed. We found that while ambient temperature is negatively correlated with consumption in the cold winter periods, the consumption surplus is positively correlated with passenger load and generally positively correlated with the delay on the trip because of road traffic. In the case of delay, the consumption increase is caused by more frequent acceleration and the greater consumption of auxiliary systems due to longer running times. Accordingly, the energy consumption can be estimated if the characteristics data are available. The results can be used by bus service operators to plan the daily schedule and predict the energy consumption of a BEB.